Cross-perspectives of social actors on failure and drop-out of Gypsies/Roma: Focus groups in the metropolitan areas of Lisbon and Porto, Portugal - Magano, O.; Mendes, M. M. (XIII Congreso Español de Sociología: Libro de Actas, 2019)
In Portugal, schooling is a universal constitutional right for all, but in the case of the Gypsies, high rates of illiteracy and school drop-out continue to occur, despite the educational and social policies introduced after the implementation of the democratic system in Portugal (1974) and, most recently, the national strategy for the integration of Roma (2013). The fact is that the conclusion of compulsory schooling is still rare among Roma people, even among the new generations, and there is a huge gap between schooling by Gypsies and non-Gypsies, revealing inequalities in access to this constitutional right. The purpose of this communication is to present a multidimensional analysis of the perspectives of several social actors involved in the educational process in vulnerable urban spaces, based on results gathered through nine focus groups held in the metropolitan areas of Lisbon (four) and Porto (five) with the participation of teachers, technicians and Gypsies, which allow us to know and present various perspectives on schooling. These results are part of a larger qualitative study that took place between 2013 and 2015 and whose main objective was to identify and understand some of the key factors for the continuity (or drop-out) of school and the success (or failure) of the Gypsies. The confrontation of different perspectives permitted identify obstacles that favors early school leaving or the failure of Gypsy children and young people, but also allows us to see new social outlines in tackling this issue and new challenges to social integration.